1992
DOI: 10.1021/bi00122a006
|View full text |Cite
|
Sign up to set email alerts
|

EcoRI DNA methyltransferase-DNA interactions

Abstract: We present a novel strategy with synthetic hemimethylated DNA substrates containing uracil for thymine and inosine for guanosine replacements and EcoRI DNA methyltransferase to characterize the importance of major groove hydrophobic groups to the sequence-specific modification of DNA. The bacterial Mtase uses S-adenosyl-L-methionine to methylate the double-stranded DNA site 5'GAATTC3' at the N6 position of the central adenosine of each strand. Uracil substitution in either strand at the outer thymine (5'GAATUC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
3
17
0
Order By: Relevance
“…For oligonucleotides these compensation temperatures Tc are higher: for the tetradecamers studied here Tc = 330.6 K (57°C) for the melting and cooling data. This value is even higher (Tc = 360 K) for a series of nonamers (52), but of the same order (Tc = 320 K) for another series of tetradecamers (11).…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…For oligonucleotides these compensation temperatures Tc are higher: for the tetradecamers studied here Tc = 330.6 K (57°C) for the melting and cooling data. This value is even higher (Tc = 360 K) for a series of nonamers (52), but of the same order (Tc = 320 K) for another series of tetradecamers (11).…”
Section: Discussionmentioning
confidence: 79%
“…This was the case, even for dI substituting for dG, contrary to the observations of Martin et al (49) who had found that I-C base pairs were less stable than G.C and even than A.T pairs. In a recent study on hemimethylated oligonucleotides (11,50), however, the presence of I-C pairs instead of G.C pairs showed moderate to large increases in AH and AS, depending on the sequence and the (Fig. 4).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…The goal was to both extend the initial dye to dye distance so as to further remove any potential for direct protein-dye interactions, and to alter the orientation of the dye to the protein bound at the central hexanucleotide recognition segment. We previously demonstrated that M.EcoRI binds to two additional bases on each side of this recognition hexanucleotide (53), thus making contacts with 10 base pairs in the specific complex). Fig.…”
Section: Discussionmentioning
confidence: 99%